REASSOCIATION AND REACTIVATION OF GLUCOSE 6-PHOSPHATE DEHYDROGENASE FROM STREPTOMYCES AUREOFACIENS AFTER DENATURATION BY 6 M UREA (Journal of Sciences, Islamic Republic of Iran)
Glucose 6-phosphate dehydrogenase (G6PD) from Streptomyces aureofaciens was purified and denatured in 6 M urea. Denaturation led to complete dissociation of the enzyme into its inactive monomers, 98% loss of the enzyme activity, about 30% decrease in the protein fluorescence and a 10 nm red shift in the emission maximum. Dilution of urea-denatured enzyme resulted in regaining of the enzyme activity and the native protein fluorescence. The renatured enzyme was indistinguishable from the native enzyme based on a number of enzymological and physicochemical criteria. Regaining of the protein fluorescence occurred immediately after diluting the denatured enzyme and before reactivation started. The reactivation process was also monitored by measuring the accessibility of histidine residues toward diethylpyrocarbonate modification. As the reactivation proceeded, less histidine residues were able to be modified. Nicotineamide adenine dinucleotide (NAD+), nicotinamide adenine dinucleotide phosphate (NADP+) and glucose 6-phosphate stimulated the reactivation rate at different degrees. It seemed likely that specific ligands stimulated reactivation by binding to an inactive form of the enzyme leading to a different pathway of refolding. The data are consistent with a model for enzyme renaturation and reactivation in which NAD+ and NADP+ pull the enzyme toward different conformational structures.